2022
DOI: 10.1002/macp.202100428
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Bubble Nucleation by Homogeneous Crystal Nuclei in Poly(l‐Lactic Acid) Foaming

Abstract: A novel method to enhance and control bubble nucleation in poly(l-lactic acid) (PLLA) foaming, not relying on external nucleating agents, is presented. Amorphous PLLA is annealed at temperatures close to its glass transition, to allow local alignment of polymer chains in the form of nanosized aggregates, called homogeneous crystal nuclei (HCN). PLLA containing HCN is then foamed after sorption of CO 2 at 120 °C and 10 MPa. Under the chosen experimental conditions, HCN can promote growth of PLLA spherulites tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Moreover, when selecting the foaming temperature, it must be considered that a polymer's glass transition and crystallization temperatures decrease due to the plasticizing effect of CO 2 [76,77]. The presence of crystals during foaming also affects the final foam structure, as crystal formation not only boosts bubble nucleation but also decreases the CO 2 amount dissolved in the polymer because CO 2 can be dissolved only in the amorphous regions [78]. The CO 2 content also plays an important role in foam expansion, since a low CO 2 content does not lead to significant foam expansion, while larger CO 2 contents show intense shrinkage upon ageing.…”
Section: Basics Of Foaming Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when selecting the foaming temperature, it must be considered that a polymer's glass transition and crystallization temperatures decrease due to the plasticizing effect of CO 2 [76,77]. The presence of crystals during foaming also affects the final foam structure, as crystal formation not only boosts bubble nucleation but also decreases the CO 2 amount dissolved in the polymer because CO 2 can be dissolved only in the amorphous regions [78]. The CO 2 content also plays an important role in foam expansion, since a low CO 2 content does not lead to significant foam expansion, while larger CO 2 contents show intense shrinkage upon ageing.…”
Section: Basics Of Foaming Technologymentioning
confidence: 99%
“…Other strategies than the addition of external nucleation agents could be used to boost cell nucleation. Long et al [78] explored the viability of homogeneous crystal nuclei to improve and control cell nucleation and growth in PLLA foams without the addition of external nucleating agents. Amorphous PLLA was annealed at temperatures close to its glass transition temperature to favour the local alignment of polymer chains into nanosized aggregates, which they called homogeneous crystal nuclei.…”
Section: Poly (Lactic Acid) (Pla)mentioning
confidence: 99%
“…Homogeneous nucleation is rare for PLA due to the lack of reaction side-chain groups in its chemical structure. Some studies suggested that homogeneous nucleation could occur at a slow cooling rate under quiescent conditions for PLLA materials [ 41 , 42 ].…”
Section: Pla Crystallizationmentioning
confidence: 99%
“…These agents can be inorganic materials, such as talc; organic compounds, such as sorbitol; or a specific PLLA-PDLA matrix known as stereocomplex PLA. Nucleating agents in the PLA polymer matrix serve as crystallization catalysts, reducing the energy barrier for nucleation [ 41 , 43 ]. Once nucleation sites are formed during the nucleation step, crystalline domains grow in the polymer matrix.…”
Section: Pla Crystallizationmentioning
confidence: 99%